Diabetic Muscular Atrophy: Molecular Mechanisms and Promising Therapies - Shen, Yuntian; Li, Ming; Wang, Kexin; Qi, Guangdong; Liu, Hua; Wang, Wei; Ji, Yanan; Chang, Mengyuan; Deng, Chunyan; Xu, Feng; Shen, Mi; Sun, Hualin (Frontiers in Endocrinology, 2022)
Diabetes mellitus (DM) is a typical chronic disease that can be divided into 2 types, dependent on insulin deficiency or insulin resistance. Incidences of diabetic complications gradually increase as the disease progresses. Studies in diabetes complications have mostly focused on kidney and cardiovascular diseases, as well as neuropathy. However, DM can also cause skeletal muscle atrophy. Diabetic muscular atrophy is an unrecognized diabetic complication that can lead to quadriplegia in severe cases, seriously impacting patients’ quality of life. In this review, we first identify the main molecular mechanisms of muscle atrophy from the aspects of protein degradation and synthesis signaling pathways. Then, we discuss the molecular regulatory mechanisms of diabetic muscular atrophy, and outline potential drugs and treatments in terms of insulin resistance, insulin deficiency, inflammation, oxidative stress, glucocorticoids, and other factors. It is worth noting that inflammation and oxidative stress are closely related to insulin resistance and insulin deficiency in diabetic muscular atrophy. Regulating inflammation and oxidative stress may represent another very important way to treat diabetic muscular atrophy, in addition to controlling insulin signaling. Understanding the molecular regulatory mechanism of diabetic muscular atrophy could help to reveal new treatment strategies.